Choosing the harder road: Naming the challenges for families in person-centred planning. (September 2019) - Ellem, Kathy; Chenoweth, Lesley; Edwards, Ruth
Person-centred planning (PCP) has underpinned disability service provision in many Western countries for the past 30 years. For many people with an intellectual disability, family members are central to this process and are important allies in facilitating positive change. This article presents findings from an evaluation of a family resourcing and capacity building project in New South Wales (NSW), Australia. Accounts from families show the merits of such work, but family efforts can be undermined by apathy and discrimination to disability from extended family, community and service providers. Asking families to be the primary support in PCP initiatives may potentially ignore the impacts of structural and psycho-emotional disablism on all family members. For families to support people with intellectual disability in PCP, there is a need to acknowledge and respond to the material, cultural and personal challenges for all family members in planning processes.